Hubungan Durasi Duduk dengan Keluhan Low Back Pain pada Pegawai BNI KCU Metro Provinsi Lampung - Fadhilla Azra Hamidah; Dyah Wulan Sumekar Rengganis Wardani; Septia Eva Lusina (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to identify the correlation between the duration of sitting and the intensity of lower back pain (Low Back Pain) complaints among employees of BNI KCU Metro, Lampung Province. Low Back Pain is one of the most common musculoskeletal conditions and can be triggered by prolonged sitting, which increases static load and pressure on the spine. This research employed an analytical observational method with a cross-sectional approach. The study sample consisted of 51 employees selected using a total sampling technique. Data were collected using a sitting duration questionnaire and the Nordic Musculoskeletal Questionnaire (NMQ) to assess LBP complaints. The results showed that the majority of employees sat for more than 4 hours per day (86.3%) and experienced LBP complaints (94.3%). The Chi-Square test indicated a significant relationship between sitting duration and LBP complaints (p = 0.001). It can be concluded that the longer a person sits, the higher the likelihood of experiencing LBP, highlighting the need for ergonomic posture application and regular muscle stretching during work.